Working with advanced Docker operations - Smith, Randall (Packt, 2018)
"Docker has been a game changer when it comes to virtualization. It provides a fast and robust way to deploy application. It makes it easy to build and deploy applications reliable, repeatable and fast. In this video course you will learn how to manage Kubernetes to manage containers across a cluster of hosts. Next it will teach you how to monitor the health of a Docker cluster. Along the way, you will learn how to deploy your application that can be quickly scaled to meet load needs and be upgraded with little or no downtime. Next, we'll guide you on how to configure the Docker daemon, troubleshooting containers and images. We'll also teach you how to use continuous integration techniques to automatically build and test Docker images. Moving on, we will discuss use cases for containers. Each use case will highlight a particular problem and how Docker helps to solve it. Finally, you will learn how to use Kubernetes orchestration system, how to monitor your Docker cluster, How to automate your application to build, test and deploy."--Resource description page